Lokalny program rewitalizacji dla miasta Jeleniej Góry - szanse i zagrożenia - Kusiak, Józef (The Programme of Local Revitalization for the Town of Jelenia Góra - Opportunities and Threats, 2006)
The study discusses up the problem of local revitalization for the Town of Jelenia Góra. The objective of the programme becomes complex, spatial, economic and social renewal of town areas assigned for revitalization, which underwent degradation as a result of changes in political and economic system, on country as well as on the European scale and related transformations of industry structure in Poland, intensification of adverse economic and social events connected with economic changes in the resent period, but also improper management of these areas in the period prior to fundamental changes in the Polish political system in 1999. Opportunities and threats referring to the realization of the analyzed programme were assessed too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 429-443